Study of forward Z+jet production in pp collisions at $\sqrt{s} = 7$ TeV - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (Springer Berlin Heidelberg, 2014)
A measurement of the $Z(→μ^+μ^-)$+jet production cross-section in $pp$ collisions at a centre-of-mass energy $\sqrt{s} = 7$ TeV is presented. The analysis is based on an integrated luminosity of $1.0\,\text{fb}^{-1}$ recorded by the LHCb experiment. Results are shown with two jet transverse momentum thresholds, 10 and 20 GeV, for both the overall cross-section within the fiducial volume, and for six differential cross-section measurements. The fiducial volume requires that both the jet and the muons from the Z boson decay are produced in the forward direction ($2.0<η<4.5$). The results show good agreement with theoretical predictions at the second-order expansion in the coupling of the strong interaction.